Impact of raising the upper extremity siding cardiac implantable electrical devices on postoperative safety - Tomonori Takeda; Atsuhiro Tsubaki; Yoshifumi Ikeda; Ritsushi Kato; Sho Kojima; Shigeru Makita (Journal of Arrhythmia, 2023)
Abstract Background The upper extremity siding cardiac implantable electrical device tends to have a limited range of motion during the perioperative period; however, the underlying reason lacks scientific evidence. This study aimed to investigate the safety of the two methods (stepwise or early) of postoperative early upper extremity rehabilitation. Methods We retrospectively investigated 650 consecutive patients with a new implantable pacemaker (PM), implantable cardioverter‐defibrillator (ICD), cardiac resynchronization therapy (CRT), or generator exchange between March 2017 and December 2020. The limitation program was conducted from March 2017 to March 2018. The intervention program started as a stepwise protocol in April 2018 and was switched to an early protocol in December 2019. Results This study analyzed 591 patients, excluding 59 who met the exclusion criteria. The mean age was 76.0 (69.0–82.0) years; 412 (69.7%) patients had a PM, 79 (13.4%) had an ICD, and 100 (16.9%) utilized CRT. There were 155 patients in the limitation protocol, 251 in the stepwise protocol, and 185 patients in the early protocol groups. Postoperative complications occurred in 53 (9.0%) patients. There was no significant difference in the incidence of all complications between the three groups (16 patients [10.3%] vs. 26 patients [10.4%] vs. 11 patients [5.9%]). Shoulder exercise‐related complications were defined as hematoma (p = .94), lead dislodgement (p = .16), and increased pacing threshold (p = .23). General complications included wound infection (p = .51), pneumothorax (p = .27), tamponade (p = .07), and deep venous thrombosis (p = .26). Conclusion Raising of the upper extremity siding cardiac implantable electrical devices above the head did not compromise postoperative safety.